SPLMT-TE: A Software Product Lines System Test Case Tool - Lima Neto, Crescencio Rodrigues; Almeida, Eduardo S.; Meira, Silvio R. L. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2012: Anais do XI Simpósio Brasileiro de Qualidade de Software, 2012)
The product lines approach requires specific testing tools that should help to manage reusable testing assets and automate the test execution. Despite of the increasing interest by the research community regarding software testing tools, Software Products Lines (SPL) still need tools to support the testing process. This work presents briefly the results of a mapping study on software testing tool and defines the requirements, design and implementation of a software product lines system test case tool, aiming at the creation and management of test assets. A controlled experiment was also conducted to evaluate the tool effectiveness.